Chinese Classifiers and their Acquisition by Heritage Language Children: a review of empirical research - Huang, Juan (2025)
This article systematically presents findings in the field of empirical research on Chinese as a heritage language (CLH). The aim is to provide an overview of CLH children's acquisition and use of classifiers in bilingual or multilingual contexts. Based on a review of classifier-related research, this article identifies demographic characteristics, geographical distribution, techniques employed, approaches, variables, and outcomes in different grammatical domains. It also highlights limitations and areas for further research attention in the future.